Status of Nutrient Elements in Rice Grain in Relation to Silicon Accumulation Pattern During Grain Filling (Bangladesh Agronomy Journal, 2017)
Rice varieties Tadukan (indica), Nanjing 11(indica), Nipponbare (japonica) and Arborio (javanica) were tested to find out the content and accumulation pattern of Si in the hull and brown rice during the grain filling periodand the changes in the weight or the contents of N, P, K, Ca and Mg both in the hull and brown rice. The largest increment in the hull weight during heading to maturity was observed for Arborio. The content of Si in the hull and brown rice increased gradually until 30 days after heading. At maturity, the amount of Si in the brown rice was one twentieth of the hull, irrespective of the cultivars. During the GFP, the increment of Si content was highest in Arborio among the cultivars, and the increase of Si content in the hull of was more remarkable than that of Si concentration. Furthermore, Si concentration in the hull of Tadukan was comparable to Arborio, despite the low Si content. These results suggested that the high amount of Si in the hull of Arborio was accomplished by the high number of silica cells on the large grain surface rather than the increased deposition of Si in each silica cell. Both the content and concentration of N and P in the hull decreased until maturity and twas negatively related to the accumulation of Si in the hull. In brown rice, the content of these elements increased with time although the changes in concentrations were slight andmost pronounced in Arborio. Therefore, it was supposed that the heavy accumulation of Si in the hull was the cause of enhanced accumulation of other elements in the brown rice. In addition, observation of Si distribution on the abaxial surface of lemma by electron-probe X-ray microanalysis revealed heavy deposition of Si on the dentate protuberances of the hull, which was supposed to be one of the reasons for different hull weight among the cultivars.Bangladesh Agron. J. 2016 19(2): 125-137